2015
DOI: 10.17219/acem/27922
|View full text |Cite
|
Sign up to set email alerts
|

Most Recent Evidence Behind Aggregometry and Genotyping Methods as Platelet Function Testing for Tailored Anti-Platelet Treatment Among PCI Patients

Abstract: Aggregometry and genotyping are methods of platelet function testing, which can be beneficial for high-risk patients undergoing invasive cardiac procedures. An optimal level of platelet reactivity (PR) should be maintained. There are discrepancies between individuals and their response to clopidogrel, accounting for the incidence of poor responders from 5% to 44%. This phenomenon predisposes the patients to increased risk of ischaemic events and thereby overall poorer clinical outcome. Prasugrel and tricagrelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Platelet function testing has a central role in the management of patients with suspected platelet disfunction [ 1 ], as well as in patients who are at risk of thrombosis who receive anti-platelet therapy [ 12 ]. Platelet reactivity, as measured by platelet aggregometry, is a very useful tool in predicting patient response to anti-platelet therapy and in predicting the risk of restenosis following surgical interventions such as percutaneous coronary interventions [ 12 , 13 ]. The clinical applications of platelet reactivity testing has put a focus on development of novel strategies for platelet reactivity assessment [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet function testing has a central role in the management of patients with suspected platelet disfunction [ 1 ], as well as in patients who are at risk of thrombosis who receive anti-platelet therapy [ 12 ]. Platelet reactivity, as measured by platelet aggregometry, is a very useful tool in predicting patient response to anti-platelet therapy and in predicting the risk of restenosis following surgical interventions such as percutaneous coronary interventions [ 12 , 13 ]. The clinical applications of platelet reactivity testing has put a focus on development of novel strategies for platelet reactivity assessment [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…16) Most importantly, previous studies have suggested the VerifyNow system was well correlated with the gold standard light transmission aggregometry. 17,18) Increasing evidence suggests that high residual platelet reactivity detected by VerifyNow assay predicts clinical outcome and adverse cardiovascular events in patients undergoing percutaneous coronary intervention.…”
Section: Discussionmentioning
confidence: 96%
“…A wide scale of the assays for the monitoring of antiplatelet therapy including turbidimetric light transmission aggregometry (LTA), whole blood aggregometry, assessment of platelet reactivity index or bleeding time, platelet function analyzer (100), the VerifyNow system, Multiplate impedance platelet aggregometry, flow cytometric analysis of the phosphorylation state of the vasodilator stimulated phosphoprotein, flow cytometric analysis of platelet functions in general, Ichor-Plateletworks, HemoStatus device, Impact cone and plate(let) analyzer, or thromboelastography (TEG) are recently available in clinical practice. [ 6 ] Rotation thromboelastometry (ROTEM) is a new viscoelastometric point-of-care-test for the complex evaluation of changes in hemostasis recently introduced to clinical practice. [ 7 ] This assay allows quick complex testing of hemostasis in one blood sample.…”
Section: Introductionmentioning
confidence: 99%